Hydrophenylation of internal alkynes with boronic acids catalysed by a Ni–Zn hydroxy double salt-intercalated anionic rhodium(iii) complex. Issue 3 (17th September 2015) - Hara, Takayoshi; Fujita, Nozomi; Ichikuni, Nobuyuki; Wilson, Karen; Lee, Adam F.; Shimazu, Shogo
Abstract : [Rh(OH)6 ] 3− intercalated Ni–Zn mixed basic salt (Rh/NiZn) acts as an efficient catalyst for the hydrophenylation of internal alkynes with arylboronic acids under mild conditions. Abstract : [Rh(OH)6 ] 3− intercalated Ni–Zn mixed basic salt (Rh/NiZn) acts as an efficient catalyst for the hydrophenylation of internal alkynes with arylboronic acids under mild conditions. The turnover number per Rh site approached 740 in the reaction between 4-octyne and phenylboronic acid. The catalytic monomeric Rh(iii ) complex is stabilised within the NiZn interlayers, attributable to a strong electrostatic interaction, promoting its re-use.